Cultivation, Diversity and Bio-Potential of Salix in the Kashmir Himalaya, India - Lubna Andleeb; Dar AR; Akhter A; Qureshi IA; Shah NH; Wani MR; Mudasir Roshan (International Journal of Life Sciences, 2018)
Represented by about 450 species in the world, genus Salix (Salicaceae) is mainly distributed in the temperate regions of the Northern Hemisphere. Salix has been regarded as a platinum crop worldwide and presently its production on large scale is meant for best possible return in yield and profit. Salix plays a dominant role in shaping economy of the State of Jammu & Kashmir as it provides raw material for handicrafts, horticulture, sports, ply board industries besides, providing fodder for cattle and sheep and also utilized as fire wood. Keeping in view its importance, various Salix species/cultivars were cultivated for three consecutive years under Short Rotation Coppice (SRC) method to record the growth in various attributes (leaf size, no. of branches per cutting, length of branches and no. of leaves per branch). Target accessions showed increase in biomass in all the attributes which was highest in the third year of cultivation. DNA finger printing technique- Amplified Fragment Length Polymorphism (AFLP) applied to characterize and understand the genetic relationship, revealed prominent diversity among studied species/cultivars of Salix. This study is imperative in developing a standard protocol for optimal utilization of abundant willow resources of the State for maximum biomass production in order to efficiently sustain the supply of raw material to potential industries for the manufacture of bio-fuels, bio-energy, bio-medicine, bio-crafts etc.